Türkiye'de İktisadi Gelişme Şoklarının İncelenmesi Üzerine Ampirik Bir Analiz - Erdoğan, Sinan (Muş Alparslan Üniversitesi, 2020)
The main goal of this paper is to investigate nature of the economic development shocks in Turkey’s economy from 1990 to 2018 by implementing set of unit root/stationarity tests. Empirical results are as follows: (a) According to the traditional unit root and stationarity tests results, the effects of shocks that can be seen in economic development are mostly permanent, (b) the results of unit root/stationarity tests with structural break indicate that the impact of economic development shocks is permanent. It can be said that the effects of possible shocks on economic development in Turkey are permanent, and economic development could not revert back its average and trend path without exogenous intervention. Therefore, stabilizing policies are required on economic development.

Bu çalışmanın temel amacı, Türkiye ekonomisinde iktisadi gelişme şoklarının doğasını 1990-2018 dönemi için geleneksel ve yapısal kırılmalı birim kök ve durağanlık testleriyle araştırmaktır. Ampirik bulgular şöyle özetlenebilir: (a) geleneksel birim kök testi sonuçları iktisadi gelişmede görülebilecek şokların etkilerinin büyük oranda kalıcı olduğunu göstermektedir, (b) yapısal kırılmalı birim kök testleri sonuçları da iktisadi gelişme şoklarının etkisinin kalıcı olduğuna işaret etmektedir. Bu bulgular ışığında, Türkiye’de iktisadi gelişme üzerinde muhtemel şokların etkisinin kalıcı olduğu, bir diğer ifadeyle iktisadi gelişmenin herhangi bir şok durumunda dışsal müdahale olmaksızın ortalama değerine ve trend patikasına dönemediği ifade edilebilir. Bu bulgular, Türkiye’de iktisadi gelişme üzerinde dengeleyici politikaların gerekliliğine işaret etmektedir.
An Empirical Analysis on Investigation of Economic Development Shocks in Turkey
anemon
Keywords: Economic Development; Economic development Shocks; Turkey; Structural Break; Unit Root; İktisadi Gelişme; İktisadi Gelişme Şokları; Türkiye; Yapısal Kırılma; Birim Kök